Adverse events of smoking cessation treatments (nicotine replacement therapy and non-nicotine prescription medication) and electronic cigarettes in the Food and Drug Administration Adverse Event Reporting System, 2004−2016. (21st May 2018) - Motooka, Yumi; Matsui, Toshinobu; Slaton, Rachel M; Umetsu, Ryogo; Fukuda, Akiho; Naganuma, Misa; Hasegawa, Shiori; Sasaoka, Sayaka; Hatahira, Haruna; Iguchi, Kazuhiro; Nakamura, Mitsuhiro
Objectives: Several smoking cessation treatments (nicotine replacement therapy and non-nicotine prescription medication) and electronic cigarettes are widely used. We evaluated the adverse events related to smoking cessation treatments and electronic cigarettes in the US Food and Drug Administration Adverse Event Reporting System database. Methods: We analyzed reports of adverse events associated with smoking cessation treatment and electronic cigarettes terms dated between January 2004 and December 2016. We used the reporting odds ratio with 95% confidence intervals to detect a signal for each adverse event. Results: In total, 8, 867, 135 reports in the Food and Drug Administration Adverse Event Reporting System database were analyzed. The numbers of adverse events for nicotine replacement therapy (transdermal, buccal, oral, and respiratory administration) were 1673, 1016, 425, and 56, respectively. Nicotine replacement therapy (transdermal, buccal, and oral) demonstrated adverse events of nausea, nicotine dependence, and dizziness. For nicotine (transdermal) exposure, the top 5 adverse events reported were nausea (149 cases, reporting odds ratio: 2.28 (95% confidence interval: 1.92–2.69)), dizziness (132 cases, reporting odds ratio: 3.04 (95% confidence interval: 2.54–3.63)), application site erythema (108 cases, reporting odds ratio: 32.52 (95% confidence interval: 26.74–39.55)), headache (98 cases, reporting odds ratio: 1.84 (95% confidence interval: 1.50–2.25)), and dyspnea (94 cases, reporting odds ratio: 1.93 (95% confidence interval: 1.57–2.38)). Many cases of improper use of nicotine replacement therapies were reported. Nausea, depression, abnormal dreams, insomnia, and other adverse events were reported for varenicline. Insomnia, rash, anxiety, and dizziness were reported for bupropion. We observed electronic cigarettes–related adverse events such as dizziness, dyspnea, nausea, heart rate increased, and tremor. Conclusion: Our findings suggest that an association exists between nicotine-related adverse events and nicotine replacement therapy. Healthcare professionals should closely monitor smokers trying to quit nicotine use for the misuse of nicotine replacement therapy. These findings may be informative to healthcare professionals in order to improve the management of smoking cessation treatment.